Rapid shifts in the thermal sensitivity of growth but not development rate causes temperature–size response variability during ontogeny in arthropods. Issue 6 (23rd January 2019) - Horne, Curtis R.; Hirst, Andrew G.; Atkinson, David; Almeda, Rodrigo; Kiørboe, Thomas
Abstract : Size at maturity in ectotherms commonly declines with warming. This near‐universal phenomenon, formalised as the temperature–size rule, has been observed in over 80% of tested species, from bacteria to fish. The proximate cause has been attributed to the greater temperature dependence of development rate than growth rate, causing individuals to develop earlier but mature smaller in the warm. However, few studies have examined the ontogenetic progression of the temperature–size response at high resolution. Using marine planktonic copepods, we experimentally determined the progression of the temperature–size response over ontogeny. Temperature–size responses were not generated gradually from egg to adult, contrary to the predictions of a naïve model in which development rate was assumed to be more temperature‐dependent than growth rate, and the difference in the temperature dependence of these two rates remained constant over ontogeny. Instead, the ontogenetic progression of the temperature–size response in experimental animals was highly episodic, indicating rapid changes in the extent to which growth and development rates are thermally decoupled. The strongest temperature–size responses occurred temporally mid‐way through ontogeny, corresponding with the point at which individuals reached between 5 and 25% of their adult mass. Using the copepod Oithona nana, we show that the temperature‐dependence of growth rate varied substantially throughout ontogeny, whereas the temperature dependence of development rate remained constant. The temperature‐dependence of growth rate even exceeded that of development rate in some life stages, leading to a weakening of the temperature–size response. Our analyses of arthropod temperature–size responses from the literature, including crustaceans and insects, support these conclusions more broadly. Overall, our findings provide a better understanding of how the temperature–size rule is produced over ontogeny. Whereas we find support for the generality of developmental rate isomorphy in arthropods (shared temperature dependence of development rate across life stages), this concept appears not to apply to growth rates.